Pengaruh Manajemen Material Terhadap Produktivitas Kerja Pada Pekerjaan Pembangunan Mall Pelayanan Publik Gowa - Ashar, Ahmad; Abduh, M. Natsir; Yuniarto, Eka (Program Studi Teknik Sipil Universitas Bosowa, 2025)
Low labor productivity in a construction project can have a negative impact, such as causing project delays so that the project is not completed on time, therefore this study aims to identify factors in material management that affect labor productiveness. The type of research used is a quantitative approach with the survey method and analyzed with the double linear regression analysis operated with the Statical Program for Social Science (SPSS) program. The double lineary regression is used to trace patterns of relationships between bound variables with two or more free variables. Based on the regression model obtained the output value of F sig. 0,000 smaller than 0.05 stated that material delivery, material usage, material storage and Quality Control together (simultaneously) influence the (Y) productivity variable. The factor that has the most dominant influence on the productivity of the project is the Material Delivery Variable (X1) with a significance of 0.001 with a R-square value of 0.428 which means 42.8% of the influence of X1 on Labor Productivity (Y) and the Material Usage Variabel (X2) signifying value of 0,000 with the R-Square of 0.557 which means a large 55.7% of the impact of X2 on Labor Produktivity. (Y).